Depression, anxiety, stress, and fear of COVID-19 among Bangladeshi medical students during the first wave of the pandemic: a mixed-methods study - Ashiq, Md Ashiqur Rahman; Gupta, Pradip Sen; Jubayer Biswas, Md Abdullah Al; Ahmed, Nowreen; Sultana, Mst. Sadia; Ghosh, Bikona; Hasan, M. Tasdik (Frontiers in Psychiatry, 2023)
Aim: This study aims to investigate depression, anxiety, stress, and fear of the COVID-19 pandemic and the associated risk factors among Bangladeshi medical students. It also explored qualitative insights on mental health during the first wave of the pandemic from medical students. Methods: This mixed-methods study was conducted online in Bangladesh from June 2020 to September 2020. Participants were Bangladeshi medical students from 1st year to the final year. The quantitative part included a structured online survey. One focus group discussion (FGD) was organized using the Zoom platform to collect qualitative insights from the students. To determine stress, anxiety, and depression, the Bangla validated version of the Depression, Anxiety, and Stress Scale 21 (DASS-21) was used. A 7 item and Bangla validated Fear of COVID-19 Scale, also known as FCV-19S, was used to explore the COVID-19 specific fear of the students. A semi-structured topic guide was used for exploring the qualitative insights of medical students. Results: The study reported that 51.20%, 59.40%, and 64% of the 406 respondents had moderate to severe stress, anxiety, and depressive symptoms respectively according to the DASS-21. The mean score of the fear for the COVID-19 scale was 19.4 (SD 6.4). Respondents who had 50+ years aged family members (B=2.1; CI: 0.3-3.9) and infected family members (B= 1.9; 95% CI: 0.1-3.7) displayed a higher fear of COVID-19. Altered sleep was a potential risk factor for developing stress, anxiety, and depression symptoms. Manual thematic analysis of qualitative data generated four major themes including perception on fear of COVID-19, perception on mental health impacts during COVID-19, change in medical curriculum along with pandemic and recommendations from the medical students to support mental health concerns of medical students during public health crisis like this pandemic. Conclusion: A substantial proportion of medical students experienced mental health difficulties in Bangladesh. Appropriate interventions should be designed, and adequate support should be provided to the medical students to protect their mental health & wellbeing considering the potential impact of them on the future health system in a low resource setting like Bangladesh.